2018
DOI: 10.1177/0022042618786717
|View full text |Cite
|
Sign up to set email alerts
|

Rural and Urban Differences in Nebraskans’ Access to Marijuana, Methamphetamine, Heroin, and Prescription Pills

Abstract: The ability of a user to access a given type of drug is related to the configuration of the market for that drug, and a range of economic and criminal justice concerns. This study focuses on Nebraskan’s “ready access” to four types of drugs (marijuana, methamphetamine, heroin, and prescription pills) in 2016, using a statewide survey of housed Nebraskan adults. Ready access is defined as a participant knowing at least one person from whom they could obtain a given type of drug if they wanted to. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Our finding that kratom use was associated with a slightly decreased likelihood of residence in an urban/suburban (vs. rural) area warrants focused attention. It may be that persistent barriers to SUD treatment in rural regions hard hit by the opioid epidemic (Andrilla et al, 2017; Jones et al, 2018; Keyes et al, 2014; Luu et al, 2018; Prunuske et al, 2014) have led some rural residents to try kratom as a form of self-treatment, or that the characteristics of rural drug markets, compared to urban ones, make kratom an appealing form of withdrawal mitigation when preferred drugs cannot be readily obtained due to cost, accessibility (e.g., driving long distances), or supply disruptions (e.g., increased opioid prescribing guidelines and monitoring), which have changed in rural drug markets over the past decade (Cicero et al, 2007; Habecker et al, 2018; Havens et al, 2007; Lebin et al, 2019; Monnat et al, 2019; Moody et al, 2017; Patrick et al, 2016, 2019; Sexton et al, 2008; Surratt et al, 2014). Heroin, despite its proliferation, still cannot be obtained as cheaply and readily in most rural compared to urban areas; whereas kratom can be purchased online and at a variety of in-person retail shops.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that kratom use was associated with a slightly decreased likelihood of residence in an urban/suburban (vs. rural) area warrants focused attention. It may be that persistent barriers to SUD treatment in rural regions hard hit by the opioid epidemic (Andrilla et al, 2017; Jones et al, 2018; Keyes et al, 2014; Luu et al, 2018; Prunuske et al, 2014) have led some rural residents to try kratom as a form of self-treatment, or that the characteristics of rural drug markets, compared to urban ones, make kratom an appealing form of withdrawal mitigation when preferred drugs cannot be readily obtained due to cost, accessibility (e.g., driving long distances), or supply disruptions (e.g., increased opioid prescribing guidelines and monitoring), which have changed in rural drug markets over the past decade (Cicero et al, 2007; Habecker et al, 2018; Havens et al, 2007; Lebin et al, 2019; Monnat et al, 2019; Moody et al, 2017; Patrick et al, 2016, 2019; Sexton et al, 2008; Surratt et al, 2014). Heroin, despite its proliferation, still cannot be obtained as cheaply and readily in most rural compared to urban areas; whereas kratom can be purchased online and at a variety of in-person retail shops.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Centers for Disease Control and Prevention (2018), usage rates for opioids are quite similar across rural, urban, and metropolitan areas, while methamphetamine use is greatest in rural communities. In their survey of Nebraskans, Habecker et al (2018) found that compared to urban users, rural drug users began using drugs at an earlier age and were more likely to use and sell methamphetamine. Rural methamphetamine users also used riskier methods; up to one-half of rural Nebraska methamphetamine users preferred injection-based use, a rate that is twice that of urban methamphetamine users (Grant et al, 2007;Habecker et al, 2018).…”
Section: Rural Spacesmentioning
confidence: 99%
“…In their survey of Nebraskans, Habecker et al (2018) found that compared to urban users, rural drug users began using drugs at an earlier age and were more likely to use and sell methamphetamine. Rural methamphetamine users also used riskier methods; up to one-half of rural Nebraska methamphetamine users preferred injection-based use, a rate that is twice that of urban methamphetamine users (Grant et al, 2007;Habecker et al, 2018). In their study of nearly 19,000 adolescents from communities of less than 50,000, Rhew et al (2011) found that middle and high schoolers living on a farm in rural communities had the highest use rates of alcohol, cigarette, marijuana, smokeless tobacco, inhalant, and other illicit drugs, followed by middle and high schoolers living in rural communities but not on a farm, and those who live in a town, respectively.…”
Section: Rural Spacesmentioning
confidence: 99%
See 1 more Smart Citation